2001
DOI: 10.1107/s002188980101086x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional imaging of crystal defects by `topo-tomography'

Abstract: A new technique,`topo-tomography', suitable for the characterization of the three-dimensional defect structure in bulk crystals, is proposed. The technique consists of the combination of diffraction topography and microtomography. It is applicable to high-quality single crystals, provided that the`direct image' is the dominant contrast mechanism. In this case, crystal defects give rise to locally enhanced intensity compared with the perfect-crystal matrix. The additional intensities sum along the diffracted-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(80 citation statements)
references
References 9 publications
0
74
0
2
Order By: Relevance
“…X-rays provide an alternative means of characterizing dislocations in the bulk without the need for sectioning. X-ray topography, which relies on the extinction contrast formed when the crystal lattice moves out of the Bragg condition, allows bulk single dislocation imaging 12 . However, it is confined to samples with small lattice rotations and low dislocation densities, and does not provide direct quantitative information, greatly limiting its range of applications.…”
mentioning
confidence: 99%
“…X-rays provide an alternative means of characterizing dislocations in the bulk without the need for sectioning. X-ray topography, which relies on the extinction contrast formed when the crystal lattice moves out of the Bragg condition, allows bulk single dislocation imaging 12 . However, it is confined to samples with small lattice rotations and low dislocation densities, and does not provide direct quantitative information, greatly limiting its range of applications.…”
mentioning
confidence: 99%
“…Ludwig has suggested that one could combine diffraction with microtomography by applying the same geometry as in topo-tomography 2 [18]. The pro-2 Topo-tomography is a novel technique due to Ludwig and coworkers [18].…”
Section: Grain Mapping On the Basis Of Extinction Contrastmentioning
confidence: 99%
“…The pro-2 Topo-tomography is a novel technique due to Ludwig and coworkers [18]. It is an extension of conventional x-ray topography, which allows visualization of longrange strain fields, induced, for example, by crystalline defects such as inclusions or individual dislocations [19,20].…”
Section: Grain Mapping On the Basis Of Extinction Contrastmentioning
confidence: 99%
“…In the early stages of the development of X-ray topographic techniques, stereotopographs were often recorded as a pair in the hkl and -h-k-l reflections [3], or recorded as a pair rotated by 781 about the diffraction vector [4]. Recently, a new technique, topo-tomography, has been developed at the ID-19 beamline of the European Synchrotron Radiation Facility (ESRF, Grenoble, France), which combines tomography and topographic imaging [5]. The technique has allowed us to analyze the configuration of individual dislocations inside a low-absorbing high-quality single crystal, e.g.…”
Section: Introductionmentioning
confidence: 99%